2023
DOI: 10.1021/acscatal.3c03329
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Role of Silyl and Silane in Si–Ni Catalysts for Hydrogenation

Yinwu Li,
Huayu Liang,
Yubang Liu
et al.

Abstract: Transition-metal complexes with Si−M bonds are important catalysts for hydrosilylation and hydrogenation reactions. However, the function of the ligated silicon atom in the organosilicon metal catalysts remains unknown. Herein, we unravel the intriguing role of silyl and silane types of active modes in the Si−Ni complexcatalyzed selective hydrogenation of alkyne. Comprehensive density functional theory calculations were performed to investigate the nickel hydride insertion, silicon hydride migration, H 2 metat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Their results suggested that the interconversion between silyl (Si–Ni–H) and silane (η 2 -Ni–H) would have a significant influence on the reactivity and selectivity of the alkyne hydrogenation reaction. 69 In short, this theoretical work not only enriched the understanding of X-type silyl ligands in transition-metal catalysis but also highlighted the versatility and effectiveness of silyl ligands in stabilizing transition metal centres.…”
Section: Small Molecule Activationmentioning
confidence: 86%
“…Their results suggested that the interconversion between silyl (Si–Ni–H) and silane (η 2 -Ni–H) would have a significant influence on the reactivity and selectivity of the alkyne hydrogenation reaction. 69 In short, this theoretical work not only enriched the understanding of X-type silyl ligands in transition-metal catalysis but also highlighted the versatility and effectiveness of silyl ligands in stabilizing transition metal centres.…”
Section: Small Molecule Activationmentioning
confidence: 86%
“…40,41 The reliability of this method for TM system calculations has been verified through various theoretical and experiment research studies. 23,34,42–45 The unrestricted formalism of the M06-L functional was adopted to calculate the high spin states ( S > 0). The def2-SVP basis set was selected for C, H, N, and O atoms, and the Stuttgart/Dresden (SDD) basis set was utilized to describe Fe, Co, and Ni atoms, both of which are commonly used basis sets for the corresponding systems.…”
Section: Methodsmentioning
confidence: 99%
“…The def2-SVP basis set was selected for C, H, N, and O atoms, and the Stuttgart/Dresden (SDD) basis set was utilized to describe Fe, Co, and Ni atoms, both of which are commonly used basis sets for the corresponding systems. 43–47 The Grimme's DFT-D3 scheme was used to deal with the long-range van der Waals (vdW) interactions. 48 The vibrational frequency calculations were added for: (1) confirming geometrical structures as minima (zero imaginary frequency); (2) verifying the accuracy of the geometries for the transition state (TS, only one imaginary frequency); (3) providing free energies at 298.15 K. The intrinsic reaction coordinates (IRC) were also performed to verify that the configurations of TS connect two relevant minima.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of direct hydrogen transfer, the solid catalysts having electron-deficient Lewis acidic site and basic site play a crucial role in catalyzing CTH reactions by forming a six-membered ring intermediate. This mechanism is commonly known as the Meerwein–Ponndorf–Verley (MPV) mechanism. , While in the case of metal hydride transfer pathway, hydrogenation is generally catalyzed by a transition-metal catalyst by forming metal hydride bonds. When molecular hydrogen is used as a hydrogen source, it is absorbed on the surface of the catalyst and considered as chemically equivalent hydrogen species. When liquid hydrogen is used as a hydrogen source, the acidic site of the metal forms a metal hydride bond with the liquid hydrogen and catalyzes hydrogenation reactions. For example, Ma et al utilized Cu/ZrOCO 3 for the transfer hydrogenation of methyl levulinate (ML) to γ-valerolactone (GVL) and 1,4-pentanediol (1,4-PDO) by using isopropanol (IPA) as a hydrogen source.…”
Section: Dissociation Of Molecular H2 and Other Hydrogen Sources Over...mentioning
confidence: 99%